Prevalence of Self-Medication among First Year Medical Students in Government Medical College at Jamnagar, Gujarat (GAIMS Journal of Medical Sciences, 2025)
Background: Self-medication is medication taken by person without professional advice. MBBS students are future professionals but during first year they don’t have proper knowledge about different medications. So, during first year of study, they are more vulnerable to self-medication and their potential side effects.Material and methods: Pretested structured validated self-medication questionnaire was used in this study.Results: We have found that out of 360 participants 289 (80.30%) students accepted that they had taken self-medication within one-year duration after taking admission in first year MBBS.Conclusion: Self-medication is present in medical students prior to any proper knowledge about hazards of medications. Students should be properly guided about self-medication and their hazards during their first year MBBS study to protect them from self-medication inflicted hazards.